Retention of increased maximum oxyregulation capacity in corals transplanted from an extreme mangrove environment to a reef flat - Dilernia, Nicole J.; Suggett, David J.; Roper, Christine D.; Alderdice, Rachel; Voolstra, Christian R.; Kühl, Michael; Camp, Emma F. (My University, 2025)
Loss of oxygen (O2) from the world's oceans to physiologically-critical levels (“hypoxia”) is an important, yet understudied stressor for coral reefs. However, extreme reef-neighbouring ecosystems such as mangrove lagoons that are routinely subjected to frequent low-pO2 exposure (i.e., low partial pressure of O2), high temperature fluctuations, and low-pH, may be harbouring corals with a higher capacity for oxyregulation, rendering them more resilient to adapt to life in low-pO2 surroundings. We investigated differences in the hypoxic response of the common reef-building coral Pocillopora acuta following 1-year transplantation between Low Isles reef flat (a comparatively more stable O2 environment) and Woody Island mangrove lagoon (a more variable and oftentimes low-pO2 habitat), on the Great Barrier Reef. Analysing hypoxia response curves and metabolic function and physiology, we found that mangrove P. acuta retained attributes for hypoxic tolerance when transferred between habitats. These corals survived frequent low-pO2 exposure (<1.77 mg O2 L−1), and although total positive regulation (Tpos) was similar between all coral populations, mangrove-to-reef transplants exerted their maximum regulation capacity (Pcmax) at a lower pO2 than all other groups, even after 1-year in a more typical O2 environment. Gene expression analyses also revealed activation of non-hypoxia inducible factor target pathways in mangrove corals as an alternative means of anaerobic respiration. The ability of coral populations from extreme ecosystems to exert maximum regulation capacity at low-pO2 may therefore be a long-term conserved property, based on greater O2 metabolisation, highlighting tolerance of mangrove P. acuta to survive extreme O2 conditions in this mangrove environment.
Keywords: 570